Cooperative integrated reading composition to improve students reading comprehension achievement, motivation an interest - Salina Ahdia Fajrina (2018)
The study aimed to determine the effect of Cooperative Integrated Reading Composition (CIRC) to improve students reading comprehension achievement, motivation, and interest. A quantitative approach with a quasi-experimental design was used for this study. Interviews were also used to support the quantitative data. A total of 54 fifth grade students from the district of Kalimantan, Banjar, Indonesiawere involved in the study. There were 28 students in the experimental group and 26 students in the control group. Quantitative data were collected from the pre and posttests and surveys, while the qualitative data came from the interviews. The quantitative data were analyzed by using descriptive and inferential analyses. Descriptive analysis showed the frequencies, means, and standard deviation, while the inferential statistics involved an independent t-test. The findings of the pre and posttests showed that there was a significant improvement in achievement for the experimental group (M=91.96, SD=5.33) when compared to the control group (M=85.38, SD=5.28), t(52)=4.55, p<0.05. The result also showed that the level of motivation for the experimental group (M=59.96, SD=6.40) was significantly higher than the control group (M=35.92, SD=6.29), t(52)=12.16, p<0.05. Analyses of students interest in reading showed a higher rate of interest for the experimental group (M=55.92, SD=6.82) when compared with the control group (M=35.81, SD=6.02), t(52)=12.19, p<0.05. Interview data indicated that students enjoyed reading when the teacher used CIRC in the classroom. This study showed that the use of CIRC could enhance the students reading comprehension in Bahasa Indonesia. In addition, CIRC had a positive impact on the students reading comprehension of Bahasa Indonesia in terms of achievement, motivation and interest.